Pengaruh Brand Awareness dan Brand Image Terhadap Loyalitas Pelanggan dengan Kepercayaan Sebagai Variabel Intervening (Studi Pada Produk Pakaian Dalam Pada Platform Tiktok) - Darojat, Adim Rofind; Lestari, Wuryaningsih Dwi (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to examine the influence of brand awareness and brand image on customer loyalty with trust as an intervening variable (Study of underwear products on the Tiktok platform). The population used in this research are customers who have purchased underwear products via the Tiktok platform. The sampling technique is carried out using probability sampling because each element of the population is considered to have the same opportunity to become a sample. This type of design uses simple random sampling where sampling from the population is done randomly. The data source was obtained from distributing questionnaires to all TikTok shop customers/users. The data collection technique used in this research is a questionnaire method for respondents, measuring the questionnaire using a Likert scale. This research uses a Structural Equation Modeling (SEM) approach using a path diagram which makes it possible to enter all observed variables via Partial Least Square (PLS) with a calculation process assisted by the SmartPLS 3.2.9 software application program. The results of this research are as follows, 1) Brand Awareness has a positive and significant influence on Customer Trust so that the first hypothesis is accepted; 2) Brand Image has a positive and significant influence on Customer Trust so that the second hypothesis is accepted; 3) Customer Trust has a positive and significant influence on Customer Loyalty so that the third hypothesis is accepted; 4) Brand Awareness has a positive and significant influence on Customer Loyalty so that the fourth hypothesis is accepted; 5) Brand Image has a positive and significant influence on Customer Loyalty so that the fifth hypothesis is accepted; 6) Brand Awareness has a positive and significant influence on Customer Loyalty through Customer Trust so that the sixth hypothesis is accepted; 7) Brand Image has a positive and significant influence on Customer Loyalty through Customer Trust so that the seventh hypothesis is accepted.